Table. 18. Characteristics related to energy budget for Earth and Venus. - Mahmoud E. Yousif (20910335) (2025)
Table. 18. Some characteristics of the energy budget of both the Earth and Venus, from which, there’s an indication that, the transformation of the Venus to a planet with atmosphere 96.5% composed of carbon dioxide (CO2), which posed a big question, is it possible that, all materials in Venus had once ignited and transformed into this huge CO2?